Near resonant and nonresonant third-order optical nonlinearities of colloidal InP/ZnS quantum dots - Wang, Y. (2013)
We have investigated the third-order optical nonlinearities of high-quality colloidal InP/ZnS core-shell quantum dots (QDs) using Z-scan technique with femtosecond pulses. The two-photon absorption cross-sections as high as 6.2 x10^3 GM are observed at 800 nm (non-resonant regime) in InP/ZnS QDs with diameter of 2.8 nm, which is even larger than those of CdSe, CdS, and CdTe QDs at similar sizes. Furthermore, both of the 2.2 nm and 2.8 nm-sized InP/ZnS QDs exhibit strong saturable absorption in near resonant regime, which is attributed to large exciton Bohr radius in this material. These results strongly suggest the promising potential of InP/ZnS QDs for widespread applications, especially in two-photon excited bio-imaging and saturable absorbing.